STATUS KENEGARAAN (STATEHOOD) NEGARA – NEGARA KEPULAUAN BERDATARAN RENDAH (LOW-LYING ISLAND NATIONS) YANG SELURUH WILAYAHNYA TERENDAM AIR LAUT - Paulina Tandiono; Suhaidi Suhaidi; Arif Arif (Journal of USU International Law, 2014)
ABSTRACT Throughout the development of the international community, never before has a country vanished physically. However, the drastic climate change over the last few decades is threatening the occurrence of such phenomenon. Climate change has led to increased temperature in the earth and causes ice and snow to melt rapidly. However, the most alarming consequence is the rise of sea levels around the world. Rising sea levels will bring a serious impact, particularly on small low-lying island nations whose average height is merely a few meters above the sea. In fact, the territories of the states may even be completely submerged under sea water. This situation raises complex questions under international law, namely whether such states could still maintain their statehood in the aftermath of a complete submergence, considering the fact that in its Article 1, Montevideo Convention on the Rights and Duties of States requires territory, among others, as a condition of statehood. The present thesis delves into an overview of statehood and its criteria based on international law as well as the statehood of low-lying island nations whose territories are entirely submerged under sea water. The method employed in writing this thesis is library research technique, which is conducted by collecting materials from books, journals, internet, international legal instruments and other scientific papers that are closely related to the intent and purposes of the preparation of this thesis. Article 1 of Montevideo Convention, as acknowledged by numerous scholars, has indeed served as a benchmark in assessing statehood. However, throughout its development, there have been numerous instances in which countries do not meet some of the requirements stipulated under Montevideo Convention yet they do not lose their statehood and continue to be recognized. As it turns out, given the importance of ​​statehood, the international community has preferred to embrace the Doctrine of Presumption of State Continuity, whereby states retain their statehood despite any major changes that occur therein. In addition, as the entire submergence of a state has never happened before, the sui generis situation or unique situation of the low-lying island nations should call for a unique response too. Keywords: Statehood, State, Territory, Submergence